2023
DOI: 10.3233/jpd-230029
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complex Phenotypes of Impaired Finger Dexterity in Mild-to-moderate Stage Parkinson’s Disease: A Time-Series Analysis

Pattamon Panyakaew,
Kotchakorn Duangjino,
Apiwoot Kerddonfag
et al.

Abstract: Background: Impaired dexterity is an early motor symptom in Parkinson’s disease (PD) that significantly impacts the daily activity of patients; however, what constitutes complex dexterous movements remains controversial. Objective: To explore the characteristics of finger dexterity in mild-to-moderate stage PD. Methods: We quantitatively assessed finger dexterity in 48 mild-to-moderate stage PD patients and 49 age-matched controls using a simple alternating two-finger typing test for 15 seconds. Time-series an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Impaired dexterity has been documented as one of the earliest motor signs in PD and can be demonstrated about 6 years prior to the diagnosis of PD ( 46 ). Abnormal dexterous movements can be detected by alternating two fingers tapping on the computer keyboard or on the smartphone ( 96 , 136 , 137 ). Studies have shown that the machine learning approach using the various parameters of finger tapping tests can discriminate PD from controls with good accuracy, suggesting that the alternating finger tapping test would be a promising digital marker to quantify subtle motor symptoms in early PD ( 96 ).…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired dexterity has been documented as one of the earliest motor signs in PD and can be demonstrated about 6 years prior to the diagnosis of PD ( 46 ). Abnormal dexterous movements can be detected by alternating two fingers tapping on the computer keyboard or on the smartphone ( 96 , 136 , 137 ). Studies have shown that the machine learning approach using the various parameters of finger tapping tests can discriminate PD from controls with good accuracy, suggesting that the alternating finger tapping test would be a promising digital marker to quantify subtle motor symptoms in early PD ( 96 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The research team at ChulaPD has extensive experience in the field of digital technologies, with a track record of publication on device/sensor development and applications (96,(100)(101)(102)(103)(104). To date, the devices and technologies that have been developed have been focused on strategies for patients who have already been diagnosed with PD.…”
Section: The Value Of Digital Technologies For Parkinson's Disease As...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sip volume is another factor to consider, where the recommendation for cup sipping is about 25 ml per sip for males and 20 ml for females 30 . Impaired hand function that encompasses poor manual dexterity, reduced grip strength, and low self-perceived hand functional ability can result in delays in hand opening and pauses between the reach-grasp and take-to-lip parts of the drinking action 31 33 . Changes in hand grip anthropometry in PD is another consideration, as decreased hand grip strength is associated with decreased muscle mass and predicts functional limitations in the individuals 34 .…”
Section: Methodsmentioning
confidence: 99%
“…44 Bradykinesia in PD is currently thought to reflect a corticosubcortical network disorder implying abnormal functional connections among the fronto-basal-gangliathalamocortical motor loop and the cerebellum. [7][8][9][10]45 By contrast, parkinsonian rigidity likely arises from abnormal inputs from GPi and substantia nigra pars reticulata to the pontobulbar reticular formation, leading to hyperactive descending projections (dorsal and medial reticulospinal tracts) directed to propriospinal as well as spinal Ia and Ib interneurons. [11][12][13] This in turn results in hyperexcitability of gamma and alpha motoneurons responsible for increased muscle tone.…”
Section: Bradykinesia and Rigidity Differently Progress After Stn-dbsmentioning
confidence: 99%